White water ahead Eastman prepares for turbulent times - Holmes, Jerry D.
Jerry D. Holmes and Gary E. McGraw tell how this chemical company learned to manage change.
Once this 4 billion dollars chemical company decided that it had to grow faster, it became necessary to create an organization that constantly learned and constantly changed.
As the chemical industry headed for consolidation in the early 1990s, Eastman Chemical Company recognized that it had grow if it was to remain competitive. And to grow it had to change-immediately, before "white water" engulfed it. Choosing to manage change rather than allow change to manage it, the company decided upon a strategy that involved shifting from a functional organization to a matrixed one, while preserving its traditional strengths. Eastman chose to become a company that is market-focused, pursues global expansion, seeks faster growth, maintains functional excellence, and leverages its core competencies as never before. Eastman intends to continue reassessing and redefining itself, using the total quality management process. When it sees a turn in the river or a change in the current, it fully expects to be ready.